Synthesis Of 3,4-Methylendioxy Isoamyl Cinnamic As The Sunscreen Compound From Cullilawang Oil - Sohilait, Mario R.; Sohilait, Hanoch J.; Fransina, Eirene (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2013)
Synthesis of 3,4-methylendioxy isoamyl cinnamic as the sunscreen compound from safrole isolation of cullilawang oil had been concluded. The reactions begin from isolation safrol with reduction pressure destilation fractination yield 74.71% safrol. The isomerization of safrole to isosafrole using KOH without solvent at temperature 130Â 0C for 5 hours yield 86.50% isosafrole. The oxidation of isosafrole using KMnO4 with polysorbate (Tween 80) catalyst, yield 72.33% pyperonal crystal. The crystal of pyperonal was synthesis to become sunscreen compound of 3,4-methylendioxy isoamyl cinnamic through Claissen condensation reaction using isoamylacetate and sodium metal, yield 56.87% with 88.16% purity. The purity was tested by GC and the elucidation of those structure was analyzed by FTIR, 1H-NMR abd MS. The sunscreen efectivity of 3,4-methylendioxy isoamyl cinnamic was exam using UV-Vis spectrofotometer according to Petro method showed that the compound have a protection against UV-A light with the SPF value = 5.31